Enhancement Of Bamboo Nanofiller In Pineapple Leaf Fiber Reinforced Polyester Composites - Wahid, Zulqarnain (2016)
In this research, pineapple leaf fiber (PALF) reinforced polyester composites were developed and enhanced with nanofiller bamboo particles. Characterization of bamboo nanofiller such as surface morphologies, elemental composition and functional groups were evaluated by using Scanning Electron Microscopy equipped with Energy Dispersive X-ray Analysis (SEM with EDX) and Fourier Transform Infrared Spectroscopy (FT-IR) respectively. The SEM-EDX images revealed that bamboo nanofiller produced consisted of crushed and irregular shape structures with presence of carbon and oxygen as a major elements composition. Besides, Transmission Electron Microscope (TEM), X-ray Diffraction (XRD) and Thermogravimetric Analysis (TGA) were used to characterize particle size, crystallinity index and thermal properties of bamboo nanofiller respectively. The TEM micrograph revealed that bamboo particles size ranged between 10 to 30 nm indicates their nanometric nature. Percentage crystallinity of bamboo nanofiller by XRD analysis comes out to be 42.90%, show its lower degree of crystallinity index. Effect of different filler loading (O, l, 3, and 5 wt %) of bamboo nanofiller into pineapple leaf fiber (PALF) reinforced polyester composites were studied. The physical, mechanical, morphological and thermal properties of the composites were studied. It was observed that with incorporation of bamboo nanofiller into the composites increased its physical properties such as the density, void content and water absorption as filler loading increases.